Transcalar project of nature-based solutions for the 2030 Agenda. Innovations and interconnections - Roberta Ingaramo; Maicol Negrello; Lousineh Khachatourian Saradehi; Arin Khachatourian Saradehi (Agathón)
The essay offers a reinterpretation of nature-based solutions (NbS), viewing them not only as devices for the architectural design of urban space but also as highly efficient and cost-effective solutions capable of competing with other strategies for achieving the Sustainable Development Goals promoted by the 2030 Agenda. The authors emphasise the importance of holistically approaching the NbS project at different scales, seeing the urban fabric as a fertile ground that can accommodate adaptive solutions designed strategically and on a site-specific basis. Moreover, international case studies in this field demonstrate the potential of integrating NbS across various scales for enhancing urban resilience and promoting the preservation of the biosphere, following the Strong Sustainability Model, on which the EU Biodiversity Strategy for 2030 is also based. The discussion highlights the limitations and barriers currently slowing down the widespread application of NbS and proposes innovative solutions to overcome these issues, along with possible research scenarios.